Practising English through out-of-class language learning activities (OCLLA): EFL preparatory year students perspectives - Khaled Elkotb Elshahawy (Politeknik Negeri Bali, 2020)
The current study investigated the insights and perceptions of the EFL preparatory year students at Al-Baha University in Saudi Arabia concerning improving their English language proficiency, namely, vocabulary and grammar learning, speaking skills, listening skills, reading skills, and writing skills, through out-of-class language learning activities. The instruments of the study were pre/post-English language proficiency skills test (ELPT) and the student's weekly reflective journals (SWRJ). The study participants were 100 male students aged 18 to 20 years old. The application of the study program, Five Phases Out-of-Class Language Learning Program (FPOCLLP) lasted for three months. Paired samples t-test and the effect size were employed to collect data for the quantitative analysis. Moreover, the student's weekly reflective journals were employed to get qualitative interpretations. The findings of the study indicated that the participants' English language proficiency skills were enhanced as a result of the study program application. Finally, the study identified some recommendations and suggestions based on its results for further future research.